Desistance From Crime: Concept, Factors, and Theoretical Basis - Ilijić, Ljeposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Criminological theory, for a long time, was oriented only to the study of the causes or the aetiology of the criminal behaviour of the offender. For the last two decades, the attention of the scientific public has been increasingly preoccupied with the interest in studying the process of desistance from crime. Although researchers have not yet reached a consensus on how to define this process and a single theoretical framework, in many studies it has been described as a process of permanently stopping criminal punishments or delinquent behavior. The process of desistance from crime is an important component of the offender's criminal career, and at the same time, the least explored process. In this paper, the author devotes special attention to illuminating the process of desistance from crime, pointing to the factors that can initiate and sustain this process. Analyzing available literature, the author points out that the process of desistance is a complex and time-consuming process that is influenced by many factors, among which are the factors of aging and maturation, factors that derive from the social context and the social role of an individual, but also require changes in the level of personality and identity.